Consumers' participation in co-creating last-mile logistics : from a discordant value formation perspective - Wang, Xueqin (Nanyang Technological University, 2018)
With the proliferation of B2C e-commerce and the advancement in service technologies, logistics service providers (LSPs) are increasingly offering innovative solutions that invite end-consumers’ participation. As embodied within the concept of value cocreation (VCC), consumers contribute their resources in co-creating logistics services in the form of reverse logistics, self-collection, crowd-sourcing delivery, etc. In so doing, consumers are empowered to influence specific changes in the service offerings, whereas LSPs accrue benefits in transferring parts of the service obligations to consumers. Given the mutual benefits, the trend of VCC is expected to gain a strong development in lastmile logistics. However, the concept of VCC is not without controversies. Some VCC literature regards the concept as an idyllic market where consumers and producers live in harmony, whereas the discordant side of VCC has been underemphasised. The aim of this thesis is thus to examine the discordances of consumers’ participation in co-creating last-mile logistics. Three rounds of survey were administered and the collected data were analysed using Structural Equation Modelling. From an innovation diffusion perspective (Study 1 of this report), it is found that consumers’ attitudinal hesitation significantly influences their initial adoption intention, whereas the perceived characteristics of the co-creation interface exert differentiated impacts on consumers’ decision-making process. Consumers’ hesitation may be overcome by a sense of compatibility, simplicity and trialability of the co-creation interface as perceived by the consumers. A perception of relative advantage acts as a direct motivator that encourages consumers’ adoption. From a service fairness perspective (Study 2), the results suggest that consumers’ fairness perception is influenced by their evaluation on the service value as well as the voluntariness of their participation. More importantly, the evaluation process is shown to be biased towards consumers’ pre-formed beliefs of the participation. A positive belief (participation in logistics services is enjoyable) leads to selective processing of positive signals (service value) and disregarding negative information (involuntariness). A negative belief, on the contrary, results in significantly worsened service experiences due to biased information processing. Study 3 examines consumers’ green scepticism in response to LSPs co-creation initiatives marketed as green value propositions. It is found that consumers’ green valueorientation is not a sufficiently strong moderator in attenuating their green scepticism. It is only when LSPs also show their commitments to the environment that consumers’ scepticism (unfair perception) would be significantly reduced. In this regard, consumers’ green scepticism results in a conditional contribution to green initiatives, where a harmonious co-creation relationship can only be formed when LSPs show their genuine care of the environment. Overall, this thesis contributes to the research domain with a unified framework of consumers’ participation in co-creating logistics values. The framework aligns with innovation diffusion theory, attitude theories, service fairness theories, selective information processing theory, green consumerism / scepticism theories, which are used as theoretical anchors of this thesis. The results also caution LSPs that values may not be harmoniously formed when collaborating with consumers in service creation. It is important to build innovations, fun elements and green efforts into logistics services.